European Union Agency for Fundamental Rights: violence against women survey, 2012 (UK Data Service, 2023)
The European Union Agency for Fundamental Rights (FRA) has carried out the first survey on women's experiences of violence across the 28 Member States of the European Union (EU). The survey responds to calls of the Council of the EU and the European Parliament for comparable data on violence against women. Before the FRA survey, available data across the EU on the scale and nature of women’s experiences of violence was fragmented and with many gaps. Existing administrative data (e.g. based on incidents recorded by the police) is not comparable across countries, and many incidents are never reported to the authorities or other service providers. Results from national surveys can also not be reliably compared due to differences in question formulation and survey methodology. Furthermore, some EU Member States have not carried out national surveys on violence against women, or the available data is old. The FRA survey is based on face-to-face interviews with 42,000 women across the EU, who were selected based on random sampling. They were asked about their experiences of physical, sexual and psychological violence, including incidents of intimate partner violence ('domestic violence'). The survey also included questions on stalking, sexual harassment, experiences of violence in childhood by adult perpetrators, safety and fear of crime, as well as awareness of laws and support services. While all respondents were asked about experiencing various forms of violence in order to establish the prevalence of violence, women who had been victims of violence were asked further details about the nature and consequences of the incidents. These data can be analysed both at the EU-level and at the Member State level to assess and to develop policies to combat violence against women.